2020
DOI: 10.1093/jac/dkaa022
|View full text |Cite
|
Sign up to set email alerts
|

Trends in antimicrobial resistance among Escherichia coli from defined infections in humans and animals

Abstract: Objectives To characterize and compare resistance trends in clinical Escherichia coli isolates from humans, food-producing animals (poultry, cattle and swine) and pets (dogs and cats). Methods Antibiogram results collected between January 2014 and December 2017 by MedQual [the French surveillance network for antimicrobial resistance (AMR) in bacteria isolated from the community] and RESAPATH (the French surveillance network f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
4
8
1
1
Order By: Relevance
“…This suggests there has been a possible overall decrease in resistance in nalidixic acid, ciprofloxacin, tetracycline, sulfamethoxazole and ESBL, but an increase in resistance in ampicillin and amikacin. Our findings are similar of that found in another study from France, which found that most of the trends in antibiotic resistance in humans, pets and food-animals were either stationary or negative 30 . However, the consensus of the literature and guidance from international organisations is that antibiotic resistance is increasing globally 1 , 3 , 4 , 24 , 44 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This suggests there has been a possible overall decrease in resistance in nalidixic acid, ciprofloxacin, tetracycline, sulfamethoxazole and ESBL, but an increase in resistance in ampicillin and amikacin. Our findings are similar of that found in another study from France, which found that most of the trends in antibiotic resistance in humans, pets and food-animals were either stationary or negative 30 . However, the consensus of the literature and guidance from international organisations is that antibiotic resistance is increasing globally 1 , 3 , 4 , 24 , 44 .…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies, including a meta-analysis, have compared prevalence of resistance of simultaneously collected specimens from humans, animals and the environment. However, they have not explored the association between them, often due to methodological limitations 30 32 . Of the analyses of temporal association between sources (n = 69), 18 were statistically significant and the vast majority of these were positively associated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cain et al (2019) menyebutkan bahwa E. coli merupakan salah satu bakteri yang banyak ditemukan mengalami resistensi terhadap antibiotika golongan β-laktam, aminoglikosida, tetrasiklin dan kuinolon yang digunakan pada klinik hewan. Mekanisme resistensi pada E. coli terjadi beberapa proses yaitu dengan menutup pori-pori pada dinding sel sehingga mengurangi jumlah antibiotika yang melintasi dinding sel (Bourley et al 2020), meningkatkan produksi betalaktamase periplasmik sehingga merusak struktur betalaktam, meningkatkan output pompa (mekanisme efflux) pada transmembran sehingga bakteri dapat mengeksresikan antibiotika sebelum terjadi efek apapun, memodifikasi enzim yang menyebabkan antibiotika kehilangan kemampuan untuk berinteraksi dengan situs target yang kemudian menghambat kerja antibiotika maupun pada lipopolisakarida sehingga antibiotika tidak dapat mengikat target (Peleg & Hooper, 2010).…”
Section: Gambar 2 Zona Hambat Cakram Antibiotika Pada Muller Hinton unclassified